Plasma biomarkers of brain amyloid‐β and tau pathologies in Down syndrome. (20th December 2022) - Janelidze, Shorena; Christian, Bradley T; O'Bryant, Sid E.; Price, Julie C; Laymon, Charles M; Schupf, Nicole; Klunk, William E; Lott, Ira T; Silverman, Wayne; Rosas, H. Diana; Zaman, Shahid; Mapstone, Mark; et al.
Abstract: Background: Plasma tau phosphorylated at threonine 217 (P‐tau217) and glial fibrillary acidic protein (GFAP) are promising diagnostic and prognostic biomarkers of Alzheimer's disease (AD). We aimed to determine the usefulness of plasma P‐tau217 and GFAP to detect AD‐related pathology in individuals with Down syndrome (DS). Method: This cross‐sectional study included adults with DS (N=300) and non‐DS sibling controls (N=37) with baseline blood samples enrolled in the Alzheimer's Biomarker Consortium‐Down Syndrome study. Participants with DS all underwent plasma P‐tau217 and GFAP assessments as well as tau‐PET, β‐amyloid (Aβ)‐PET and cognitive testing. We examined association of plasma P‐tau217 and GFAP with tau‐PET, Aβ‐PET and cognitive measures using regression models and ROC curve analysis and investigated if combining P‐tau217 and GFAP together and with other plasma AD biomarkers (Aβ42/40, neurofilament light [NfL], total tau [T‐tau]) and age could improve their performance for identifying individuals with abnormal tau‐PET or Aβ‐PET. Result: Plasma levels of P‐tau217 were increased in Aβ‐PET‐positive tau‐PET‐positive (A + T + ) DS and A + T – DS compared with A – T – DS while GFAP was only increased in A + T + DS (Figure 1). Plasma P‐tau217 levels were also higher in A + T + DS than A + T – DS. In participants with DS, plasma P‐tau217 and GFAP (but not plasma Aβ42/40, t‐tau and NfL) were consistently associated with abnormal tau‐PET and Aβ‐PET status in models covaried for age (ORrange, 1.59‐2.46, p<0.028). A combination of P‐tau217 and age performed best when detecting tau‐PET abnormality in the temporal and neocortical regions (AUCrange, 0.96‐98), whereas the most parsimonious model for Aβ‐PET status included P‐tau217, T‐tau and age (AUC=0.95) (Figure 2). Higher levels of plasma P‐tau217 were associated with worse performance on DS Mental Status Examination and Cued Recall tests in Aβ‐PET positive (βrange, ‐0.231–[‐0.559], p<0.036) but not in Aβ‐PET negative DS. Conclusion: Plasma p‐tau217 is an accurate biomarker of both tau and Aβ pathological brain changes in DS that could facilitate inclusion of individuals with DS in future AD clinical trials, especially when combined with age as a covariate.